The effect of sit-stand schedules on office work productivity: A pilot study. - Lin, Jia-Hua; Bao, Stephen (Work, 2019)
BACKGROUND: Sit-stand workstations have been introduced in the workplaces to address the adverse sedentary effect inherent to typical office jobs. Existing field or laboratory studies showed that standing interventions are not a detriment to work productivity or performance. The effect of gradient standing proportion on these measures is still unknown. OBJECTIVE: The current naturalistic pilot study aimed to examine the controlled sit-stand ratio effect on office performances. METHODS: Eleven musculoskeletal symptom free office employees from a large government agency volunteered in this study. They were all equipped with electronic sit-stand desks. Computer usage (N=11) and productivity (N=3) were collected using software and organizational metrics, respectively, for four typical workdays of four different sit-stand ratios (7 : 1, 3 : 1, 2 : 1, and 1 : 1). RESULTS: There were no statistically significant schedule effects on any computer usage measures. While not significant, time using computer, keystrokes, word count, and keyboard errors were all less as standing time increased. Sit-stand ratio and job productivity did not observe a clear cause and effect relationship. CONCLUSIONS: The amount of time spent standing in typical office jobs might not affect computer usage and productivity. Further study with a larger sample is needed for a stronger evidence.